PERLINDUNGAN HUKUM PEMEGANG HAK MILIK ATAS TANAH TERHADAP PERALIHAN JUAL BELI TANAH BERDASARKAN KUASA MUTLAK - Nurul Inayah Hi Kusnadi; Dhoni Martien; Amelia Nur Widyanti (Bajang Institute, 2026)
This research examines the legal consequences of land sale and purchase agreements based on absolute power and how the legal protection of owners of land whose transfer is based on absolute power is legal. This research uses 2 legal theories, including the theory of legal consequences according to Soeroso and the theory of legal protection according to Satjipto Rahardjo. The method used in this research is normative juridical research, namely library legal research or secondary data using primary, secondary, and tertiary legal sources. The research approaches employed are the Statutory Approach, the Conceptual Approach, the Analytical Approach, and the Case Approach. The legal material collection technique involves identifying and inventorying positive legal regulations, books, journals, and other legal sources. The legal material analysis technique utilizes grammatical interpretation, systematic interpretation, analogy construction, and legal refinement construction methods. The research results show that the transfer of land rights based on absolute power is legally considered null and void because it violates the principle of freedom of contract in good faith and violates the provisions prohibiting the use of absolute power in land registration. Legal protection for holders of original property rights is provided through repressive legal measures, namely filing a lawsuit with the District Court to cancel the deed of sale and purchase agreement which is based on absolute power which was the initial agreement for the sale and purchase of the land and to return the ownership status to its original state.